Design and simulation of different excitation coil arrangements in magnetic particle imaging technique for single sided scanner - Birahim, Muhamad Fikri Shahkhirin (2021)
Magnetic particle imaging (MPI) is a new tomographic method for three-dimensional (3D) imaging by using magnetic nanoparticles (MNP) tracer. MPI consists of three important elements, which are MNP, magnetic coils and image reconstruction method. The complex topology of skin surface, coil¶s physical properties, configuration and dimension, and high input current for excitation make scanning process more difficult and limited. Image quality can be improved by enhancing the magnetic field induction generated by the excitation coil towards the MNPs¶ location. This research focused on finding alternative design for the excitation coil which can produce a strong and homogeneous magnetic field up to 0.1 mT to detect the MNPs¶ location at 10 mm to 50 mm below the skin. First, several important elements such as scanner topology, coil design parameters and deYelopment, and magnetic field induction¶s targeted distance, are needed before developing and simulating the excitation coil. Second, nine coil designs were developed and simulated using ANSYS Maxwell with different design parameter and configuration. Lastly, mathematical calculation was compared with the simulation result obtained from ANSYS Maxwell for result verification. Magnetic field induction strength, magnetic field distribution direction, and homogeneity level at specific point were considered for data analysis. This research outcome contributed to a new idea of integration of Maxwell coil pair and vertically stacked sub-coil such as in Design H that could produce a strong and homogeneous magnetic field of 17.5759 µT which was stronger compared with single excitation coil design that could only produce 9.2298 µT at the 10 mm distance below the coil. In conclusion, a portable single-sided MPI scanner with simple coil configuration, less bulky size, and low current could be developed for MPI application to produce a strong and homogeneous magnetic field induction towards the targeted MNP distances of 10 mm to 50 mm below the coil compared with the conventional MPI system. It could be an ideal tool for medical imaging application particularly to detect the breast cancer for early prevention.